2020
DOI: 10.1001/jamaneurol.2019.3812
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to Multiple Ascending Doses of the Microtubule Stabilizer TPI-287 in Patients With Alzheimer Disease, Progressive Supranuclear Palsy, and Corticobasal Syndrome

Abstract: IMPORTANCE Basket-design clinical trials that allow investigation of treatment effects on different clinical syndromes that share the same molecular pathophysiology have not previously been attempted in neurodegenerative disease.OBJECTIVE To assess the safety, tolerability, and pharmacodynamics of the microtubule stabilizer TPI-287 (abeotaxane) in Alzheimer disease (AD) or the 4-repeat tauopathies (4RT) progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 33 publications
1
78
0
1
Order By: Relevance
“…For example, TPI‐287/abeotaxane is a brain‐penetrant microtubule stabilizer that indicated efficacy in PS19 tau transgenic mice. Recent basket clinical trials on different tauopathies to test the safety, tolerability, and potential efficacy of TPI‐287 infusion indicated that (i) TPI‐287 was generally well tolerated, although anaphylactoid reactions occurred in 3/26 of AD patients, but not in 42 4‐repeat tauopathies (4RT) patients, which led to a discussion of a potential difference in sensitivity profiles of AD and 4RT patients; (ii) CSF YKL‐40 level changed in TPI‐287 groups; and (iii) the AD treatment group showed a smaller decline in MMSE scores than did the placebo group, although the difference was not significant (Tsai et al, ). Still, antimitotics remain candidate drugs for AD management.…”
Section: Effects Of Cell Cycle Interfering Drugs On Ad Modelsmentioning
confidence: 99%
“…For example, TPI‐287/abeotaxane is a brain‐penetrant microtubule stabilizer that indicated efficacy in PS19 tau transgenic mice. Recent basket clinical trials on different tauopathies to test the safety, tolerability, and potential efficacy of TPI‐287 infusion indicated that (i) TPI‐287 was generally well tolerated, although anaphylactoid reactions occurred in 3/26 of AD patients, but not in 42 4‐repeat tauopathies (4RT) patients, which led to a discussion of a potential difference in sensitivity profiles of AD and 4RT patients; (ii) CSF YKL‐40 level changed in TPI‐287 groups; and (iii) the AD treatment group showed a smaller decline in MMSE scores than did the placebo group, although the difference was not significant (Tsai et al, ). Still, antimitotics remain candidate drugs for AD management.…”
Section: Effects Of Cell Cycle Interfering Drugs On Ad Modelsmentioning
confidence: 99%
“…Currently, a variety of experimental therapeutic approaches to PSP have been proposed, mainly focused on tau protein as a target, but relatively few late-phase clinical trials have been conducted. 1,[4][5][6][7][8] Large, international clinical trials and multicenter, longitudinal, observation studies have revealed striking consistency in rates of change of clinical rating scales of PSP symptomatology, 9 particularly on the Progressive Supranuclear Palsy Rating Scale (PSPRS) and Schwab and England Activity of Daily Living scale (SEADL), 10 the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), 11 volumetric MRI measures of midbrain atrophy, 12 and cerebrospinal fluid (CSF) neurofilament light chain (NfL) concentrations. 13 This suggests that natural history data from earlier longitudinal studies could be used to gauge the potential promise of novel therapeutic interventions, before the initiation of larger, placebo-controlled trials or in situations where such trials are not practical or possible, including commonly used therapeutics, lifestyle interventions that are widely available, or other desired off-label interventions by patients and families.…”
mentioning
confidence: 99%
“…This avenue was explored by using drugs that stabilize microtubules. Promising results were obtained in tau mouse models but no beneficial effect was observed in humans ( 171 173 ). This could be explained by the fact that a recent study reported that tau does not stabilize microtubules but exerts the opposite effect ( Figure 3 ).…”
Section: Section (Iv) Hyperphosphorylated Tau: Direct or Indirect Thementioning
confidence: 99%